INTERROGATING HETEROSIS AND CONSANGUINITY FOR LIVESTOCK AND HUMAN POPULATIONS (2018)
Heterosis or hybrid vigour is an increase in the yield of a hybrid animal over those of its parents; and consanguinity, the quality of being descended from the same ancestor as another person; have been discussed independently by scholars. However, this study attempts a side by side investigation of heterosis and consanguinity as they affect livestock and human populations in antiquity and Nigeria, with a view to understanding how these cultures/strategies can positively or negatively affect the progress and prosperity of a society. The social development theory is adopted to further present an expansionary view on how society can grow and prosper with regard to these themes. The argument that heterosis or exogamy is more advantageous than consanguinity for the growth of a society is put forward in the discourse. Further studies may examine excessiveness in heterosis with regard to human development even in antiquity and Nigeria.